2015
DOI: 10.5226/jabmech.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Aspect Ratio and Flow Fields in a Rearing Tank

Abstract: Abstract-Aeration rates and tank geometry result in different larvae survival rates [1]-[6]. This study reports new results about the flow field in a rearing tank. Specifically, the effects of the aspect ratio AR (the ratio of water depth to tank radius) on overall flow fields were clarified from flow visualization and PIV (Particle Image Velocimetry) experiments. Two different types of flow patterns, a single-pair vortex system and twopair vortex system, were confirmed as the value of tank aspect ratio change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…; Sumida et al . ). Recent research in Japan has shown that another early larval mortality syndrome (‘sinking syndrome’) can be controlled by changing flow conditions in the larval rearing tanks, leading to improved and more stable larval survival of P. leopardus (Takebe et al .…”
Section: Assessment Of the Sustainability Of Grouper Aquaculturementioning
confidence: 97%
See 1 more Smart Citation
“…; Sumida et al . ). Recent research in Japan has shown that another early larval mortality syndrome (‘sinking syndrome’) can be controlled by changing flow conditions in the larval rearing tanks, leading to improved and more stable larval survival of P. leopardus (Takebe et al .…”
Section: Assessment Of the Sustainability Of Grouper Aquaculturementioning
confidence: 97%
“…Adding oil to the surface of larval rearing tanks improves survival of C. altivelis (Sugama et al 2004) by reducing mortality associated with surface-tension death, and this technique is commonly used in Indonesian hatcheries for all grouper species. Tank design, particularly tank aspect ratio, also has an influence on surface-tension death in grouper larviculture (Ruttanapornvareesakul et al 2007;Sumida et al 2015). Recent research in Japan has shown that another early larval mortality syndrome ('sinking syndrome') can be controlled by changing flow conditions in the larval rearing tanks, leading to improved and more stable larval survival of P. leopardus (Takebe et al 2011).…”
Section: Environmental and Physical Conditionsmentioning
confidence: 99%